Divided in Death - Robb, J. D. (New York Berkley Books, 2004)
Found alone on the streets as a child, Eve Dallas has built a new identity and a new future as a cop. Now the hard-edged and coolheaded detective fights for truth and justice, but she still has one very human weakness-enigmatic Irish billionaire, Roarke. And when a trusted employee of Roarke Enterprises is a suspect in a double-homicide, Roarke comes to Eve for help. Reva Ewing was a former member of the Secret Service, and now a security specialist for Roarke Enterprises-until she was found standing over the dead bodies of her husband, renowned artist Blair Bissel, and her best friend. But Lieutenant Eve Dallas believes there was more to the killing than jealous rage-all of Bissel's computer files were deliberately corrupted. To Roarke, it's the computer attack that poses the real threat. He and Reva have been under a code-red government contract to develop a program that would shield against techno-terrorists. But this deadly new breed of hackers isn't afraid to kill to protect their secret-and it's up to Lieutenant Eve Dallas to shut them down before the nightmare can spread to the whole country.
Keywords: Policewomen -- Police -- Dallas, Eve (Fictitious character)